EXPERIMENTAL STUDY OF THE PERFORMANCE CHARACTERISTICS OF SHOCK ABSORBERS - N. Batjargal; Dmitry A. Tikhov-Tinnikov; Alexander I. Fedotov (International Journal of Advanced Studies, 2023)
The article discusses the methodology for determining the performance characteristics of Toyota Prius 20 shock absorbers. The study was conducted using a stand for the diagnosis of shock absorbers developed by the Department of Road Transport of INRTU (Irkutsk National Research Technical University). Tests were carried out for five front suspension shock absorbers, one – a new serviceable shock absorber, the rest – shock absorbers that were previously in operation. The experimental dependences of the change in the resistance force of the shock absorber on the speed of movement of its rod are analyzed. The level of operational characteristics of the shock absorber under study was determined by comparing the obtained parameters with the parameters of the new shock absorber.